Characters and Characterization in Al-Saqa Mat by Yusuf Elsibai - Ensiyah Khazali; marzieh zare zardini (دراسات فی اللغه العربیه و آدابها)
Characterization is one of the important elements in fiction. The study of this element and the way it is accomplished can reflect the authors' perspectives and feelings toward the society where he lives in. Yusuf Alsibai, a modern Egyptian novelist, has produced literary works in different genres including novels, short stories and plays, with realistic and romantic slants. This study attempts to survey one of his novels Alsaqa Mat and investigate its character development the influence character development has on the development of the stories' events. There are several characters in this novel that have been modelled on lower class people in the society and have little effect in the stories' events. The author's method of characterization is an analytical-allegorical blend.  He initially describes the characters' traits from the narrator's point of view; then, he corroborates the characters' explicitly mentioned qualities by their actions, speech in the course of the story.